Accuracy of Intraoperative Transesophageal Echocardiographic Doppler Parameters in Assessing the Right Ventricular Diastolic Function After Repair of Tetralogy of Fallot in Pediatric Patients - Nagarjuna Panidapu; Saravana Babu; Baiju S. Dharan; Barsha Sen; Thomas Koshy (Annals of Cardiac Anaesthesia)
Background: This study aimed to assess the accuracy of tricuspid spectral Doppler (E/A) and tissue Doppler parameters (E/E’) to diagnose right ventricular diastolic dysfunction (RVDD) in comparison to American Society of Echocardiography (ASE criteria) in pediatric tetralogy of Fallot (TOF) patients after surgical repair. Methods: This prospective, observational study was done at a tertiary care hospital involving 40 pediatric TOF patients aged less than 2 years who underwent complete intracardiac repair with cardiopulmonary bypass (CPB). Echocardiographic observations were made using a pediatric transesophageal echocardiography probe after surgical repair in the post-CPB period. The ASE-described parameters (late diastolic forward flow in the main pulmonary artery, right atrial dilatation, inferior vena cava dilatation, and hepatic venous flow reversal) were acquired to diagnose the RVDD. The tricuspid Doppler parameters (E/A and E/E’) were measured, and its predictive ability to diagnose RVDD was analyzed and compared with the ASE criteria. Results: Based on the ASE criteria, 13 patients (32.5%) were diagnosed to have RVDD. We found that an E/E’ ratio of ≥ 6.26 and an E/A ratio of >1.34 can be taken as the cutoff for diagnosing the RVDD. Based on the tricuspid Doppler parameters (E/A > 1.34 and E/E’ >6.26), 17 patients (42.5%) were diagnosed to have RVDD, which was comparable to that of the diagnosis by ASE criteria (P > 0.05). Conclusion: The results suggested that the use of tricuspid Doppler parameters can be equally accurate and reproducible to the current ASE-described echocardiographic parameters for diagnosing RVDD after surgical repair of TOF.